The influence of perceived usefulness and e-service quality on continuance intention with user satisfactionnas a mediating variable (study on local startup Payoprint Palembang) - Tulus Wadi Nulhaq; Aslamia Rosa; Ahmad Maulana (Jurnal Mantik, 2023)
One of the cities where startups are starting to emerge is Palembang.  One of the local startups that is growing quite rapidly in the city of Palembang is Payoprint. Payoprint has been quite successful in its journey, as evidenced by the many awards it has received both on a regional and national scale. The aim of this research is to see the influence of Perceived Usefulness, E-Service Quality on Continuance Intention with User Satisfaction as a Mediating Variable (Case Study of Local Digital Startup Payoprint Palembang). This research uses a quantitative type of research using a survey method with target respondents in the Palembang area. The research subjects were consumers who had used Payoprint startup services in the Palembang area and surrounding areas. The sampling method used purposive sampling method, with a sample size of 110 respondents. The results show that there is a positive and significant influence between e-service quality and user satisfaction. The results show that there is a positive and significant influence between user satisfaction and continuance intention. The research results show that the value of the indirect influence or mediating influence of user satisfaction on perceived usefulness and continuance intention is greater than the direct influence of perceived usefulness on continuance intention. The research results show that the value of the indirect influence or mediating influence of user satisfaction on e-service quality and continuance intention is greater than the direct influence of e-service quality on continuance intention